PENDIDIKAN AKUNTANSI BERBASIS CINTA: LEPAS DARI HEGEMONI KORPORASI MENUJU PENDIDIKAN YANG MEMBERDAYAKAN DAN KONSEPSI PEMBELAJARAN YANG MELAMPAUI - Aji Dedi Mulawarman (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
The objective of this article is to enlighten and emancipate accounting education basic assumption and concept that match to the objective of national education. The objective of national education is based on balanced values of spirituality, mentality, morality, intellectuality and skill. Emancipation and enlightenments are conducted by utilizing purification (tazkiyah) methodology with fully love values.The result of tazkiyah accounting education is enlightenment and emancipation of accounting education based on self interest and secularism towards accounting education based on God interest with fully love. There are consequences of tazkiyah. First, is to free education from corporate hegemony towards education that is more corporate-responsible that extends its accountability (stakeholders, nature, and God) and empowering oriented. Second, it produces synergy of learning conception based on reproductive view learning and constructive view of learning, and beyond (hyper view of learning).